2010 IFIP Wireless Days 2010
DOI: 10.1109/wd.2010.5657753
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Random Linear Network Coding with Controlled Forwarding for wireless broadcast

Abstract: Multicasting and broadcasting are important communication techniques in wireless adhoc networks. Recently, Network Coding (NC), which has emerged as a promising technique for various applications, has been applied to multicast and broadcast in wireless adhoc networks. It is however observed that the performance using NC is strongly dependent upon the topology, node density and the kind of coding algorithm.The algorithms that are proposed are mostly dealing with single source multicasting or broadcasting.In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…The next two figures show the required number of MAC layer packet transmissions for both scenarios, with and without the support of cross-source coding. In all cases, packet delivery is high, but not 100%, as we lose packets due to collisions etc., see the results in [16]. So the MAC transmissions are normalized by the PDR to allow fair comparison across protocols with different PDRs.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next two figures show the required number of MAC layer packet transmissions for both scenarios, with and without the support of cross-source coding. In all cases, packet delivery is high, but not 100%, as we lose packets due to collisions etc., see the results in [16]. So the MAC transmissions are normalized by the PDR to allow fair comparison across protocols with different PDRs.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…We call our protocol ARLNCCF for Adaptive Random Linear Network Coding with Controlled Forwarding. The core protocol is further described in [16], where we already showed that crosssource coding reduces packet latency and increases packet delivery ratio (PDR). Here we briefly review the relevant features of the protocol and evaluate the protocol efficiency, i.e., does the protocol broadcast packets using only few MAC layer packet transmissions?…”
Section: A Cross-session Broadcast Protocolmentioning
confidence: 99%
“…The forwarding node adds its own packets with original packets and sends outgoing coded packets. Typically, RLNC performs three different operations [21], they are 1. Encoding, 2.…”
Section: Random Linear Network Coding For Unicastmentioning
confidence: 99%
“…Similarly as in ARQ technique, from (1), (11), (12), and considering the independent data received at the receivers, the average network throughput of RNC technique is represented as…”
Section: Random Network Coding (Rnc)mentioning
confidence: 99%
“…In another work, Goel et al [9] derived a lower bound of energy consumed in wireless multicast networks using NC. Further, some adaptive NC schemes have been proposed in wireless networks to increase the network throughput and bandwidth efficiency [11], [12], [13]. However, all these works did not consider prioritized data or focused only on heuristic algorithms to minimize the decoding delay of special scenarios with limited number of receivers.…”
mentioning
confidence: 99%